Viral : how social networking is poised to ignite revival - Sweet, Leonard I. (Colorado Springs, Colo. : WaterBrook Press, 2012)
Discusses how social media resources can be used to enhance relationships with fellow Christians and with God.
pt. 1. Where are we?. Logos and logo ; A tale of two cultures ; The God of creative change ; Singing strange songs in the Lord's land -- pt. 2. Twitter. In the beginning was the tweet ; Five ways Twitter can change the world -- pt. 3. Google. Jesus, master storyteller ; The infallible story ; Turning a tin ear to poetry -- pt. 4. iPhones. The advantages of whole fruit ; Trading the orange for an Apple -- pt. 5. Facebook. Cloud and fire ; Me and we in the TGIF world -- pt. 6. Googlers : a culture of revival. An infectious faith -- Conclusion : frogs, kisses, and the kingdom of God.
Includes bibliographical references (pages 199-229).
Keywords: Evangelistic work -- Computer networks; Online social networks -- Religious aspects -- Christianity